Pemberian Reward Sebagai Upaya Meningkatkan Motivasi Belajar pada Anak Usia Dini: Sebuah Tinjauan Teoretis - Maaziyah Maaziyah; Mufassirul Alam (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
Rewards as a motivational strategy can enhance children’s enthusiasm for learning, strengthen intrinsic motivation, and foster positive behavior. This study employs a descriptive qualitative method with a literature review approach, examining behaviorist, humanistic, social cognitive, and self-determination theories to understand the relationship between rewards and learning motivation. The analysis uses content analysis to identify key themes and develop a conceptual synthesis. The findings indicate that rewards not only function as positive reinforcement that encourages children’s engagement and participation in learning activities but also have the potential to cultivate intrinsic motivation when applied judiciously. Drawing on behaviorist, humanistic, social cognitive, and self-determination theories, appropriately administered rewards can promote prosocial behavior, support the fulfillment of children’s psychological needs such as autonomy and competence, and create a positive and conducive learning environment.